Eventyret Antarktis - Børde, Haakon; Johansen, Karl Hans (Gyldendal, 1978)
Keywords: Antarktis; Norge; Norsk Polarinstitutt; Sydpolsekspedisjonen; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

An eruptional model for recent lava flow on Bouvetøya, South Atlantic Ocean - Furnes, Harald; Løvlie, Reidar (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Bouvetøya; ekspedisjoner; forskning; geologi

Age relationships of Mesozoic basalt lava and dykes in Vestfjella, Dronning Maud Land, Antarctica - Furnes, Harald; Mitchell, John G (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Dronning Maud Land; ekspedisjoner; forskning; geokjemi; geologi; petrografi; vulkaner

Stratigraphy and igneous petrology of Southern Heritage Range, Ellsworth Mountains, Antarctica - Hjelle, Audun; Ohta, Yoshihide; Winsnes, Thore S (Results from Norwegian Antarctic Research 1974-1977, 1978)
Sedimentary and magmatic rocks of Late Proterozoic to Late Paleozoic age, from the southern half of Ellsworth Mountains are described. Basic volcanic rocks, mainly agglomeratic, occur abundantly in the lower part of the succession, in the Minaret Group, and in the lower part of the Heritage Group, but are not recorded in the upper part of the Heritage Group. Due to this lithostratigraphic contrast a new classification is proposed: the Heritage Group including the Middle Horseshoe Formation and the Edson Hills Formation. A stratigraphic gap is evident above the Edson Hills Formation and a separate unit–the Dunbar Ridge Formation–is proposed. This formation is of Middle-Upper Cambrian age, with trilobite-bearing limestones. The structure is governed by a major anticline with a NW plunge in the north but almost horizontal in the south. Contrast of fold intensity and fold style below the youngest exposed unit, the Whiteout Conglomerate and a weathered surface above the Crashite Quartzite suggests a late Paleozoic deformation phase. Two phases of magmatism are distinguished. The pre-Middle Cambrian magmatism is dominantly K-alkalic and suggests the beginning of block subsidence at the early stage of a rift tectonics on a continental crust. The presumptive Late Paleozoic magmatism is N-alkalic and tholeiitic, and occurred after the main deformation; however the rocks were regionally metamorphosed in the actinolite-greenschist facies probably in late Paleozoic time. This magmatism is considered to represent an advanced stage of block tectonics. (Auth. mod.)
Keywords: Antarktis; ekspedisjoner; geologi; petrologi; stratigrafi; vulkaner

Den norske Antarktis-ekspedisjonen 1976/77 - Orheim, Olav (Naturen, 1978)
Keywords: Antarktis; ekspedisjoner; forskning

Snow accumulation and snow stratigraphy on Riiser-Larsenisen, Dronning Maud Land, Antarctica - Repp, Kjell (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Dronning Maud Land; ekspedisjoner; forskning; geologi; glasiologi; isshelf; snø; stratigrafi

Weather and tide observations at Bouvetøya - Vinje, Torgny E (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Bouvetøya; ekspedisjoner; forskning; meteorologi; observasjoner; oseanografi